Walt disnep sleeping beauty story book (Grolier Books Lahore, 2020)
Princess Aurora is cursed by the evil fairy Maleficent to fall into a deep sleep on her 16th birthday after pricking her finger on a spinning wheel. A brave prince breaks the curse with a kiss, restoring peace and happiness to the kingdom. The story is a classic tale of love and destiny.